2013
DOI: 10.1097/rct.0b013e31828beb34
|View full text |Cite
|
Sign up to set email alerts
|

Three-Phase Parathyroid 4-Dimensional Computed Tomography Initial Experience

Abstract: Initial results after implementation of 4D-CT show high accuracy of interpretation for inexperienced observers, comparable to published data, and high interobserver agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…ED calculations were based on an approach including the use of a combination of two different k-factors and the corresponding scan lengths, at the anatomical areas scanned during each phase; neck (pre-contrast phase) and neck-chest (arterial phase). For the neck and chest region, k-factors within the ranges of 0.0051 to 0.0059 mSv mGy −1 cm −1 [22,[31][32][33] and 0.014 to 0.017 mSv mGy −1 cm −1 [31,39] have been suggested, respectively. However, in most previously published studies regarding CT of parathyroid glands, a single k-factor of 0.0054 mSv mGy −1 cm −1 has been used [22,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ED calculations were based on an approach including the use of a combination of two different k-factors and the corresponding scan lengths, at the anatomical areas scanned during each phase; neck (pre-contrast phase) and neck-chest (arterial phase). For the neck and chest region, k-factors within the ranges of 0.0051 to 0.0059 mSv mGy −1 cm −1 [22,[31][32][33] and 0.014 to 0.017 mSv mGy −1 cm −1 [31,39] have been suggested, respectively. However, in most previously published studies regarding CT of parathyroid glands, a single k-factor of 0.0054 mSv mGy −1 cm −1 has been used [22,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…For the neck and chest region, k-factors within the ranges of 0.0051 to 0.0059 mSv mGy −1 cm −1 [22,[31][32][33] and 0.014 to 0.017 mSv mGy −1 cm −1 [31,39] have been suggested, respectively. However, in most previously published studies regarding CT of parathyroid glands, a single k-factor of 0.0054 mSv mGy −1 cm −1 has been used [22,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous studies have shown high concordance in 4D-CT interpretations between neuroradiologists, suggesting that assignment of MGD scores is likely to be highly reproducible. 14,15 Last, a patient population presenting to a single institution may represent inherent bias. Thus, the applicability of the MGD predictive score system should also be prospectively validated in a multi-institution setting.…”
Section: Discussionmentioning
confidence: 99%